Improved on-line robotic deformation measurement and analysis - Tor, Yam Khoon. (2008)
The objectives of this project are to study the problems associated with single-station real-time deformation measurement and analysis and to develop or adopt appropriate algorithms to provide inferences of the state of the deformation in real-time.